1999
DOI: 10.1093/emboj/18.8.2119
|View full text |Cite
|
Sign up to set email alerts
|

A casein kinase I motif present in the cytoplasmic domain of members of the tumour necrosis factor ligand family is implicated in `reverse signalling'

Abstract: We have identified a putative signalling feature of the cytoplasmic domains of the tumour necrosis factor (TNF) family members based on available amino acid sequence data. A casein kinase I (CKI) consensus sequence is conserved in the cytoplasmic domain of six of 15 members of the type II integral membrane TNF ligand family. We examined the phosphorylation state of transmembrane tumour necrosis factor-alpha (mTNF) with [32P]orthophosphate labelling and in vitro kinase assays, in lipopolysaccharide-stimulated R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(138 citation statements)
references
References 46 publications
4
131
0
3
Order By: Relevance
“…We have already demonstrated that calcium mobilization and production of cytokines such as IFN-␥ and IL-2 was induced in HTLV-I-infected human T cells by the stimulation of membrane TNF-␣ (10,11). Moreover, ligation of soluble TNF receptor to membrane TNF-␣ has recently been shown to cause calcium mobilization in the mouse macrophage cell line, RAW267.4, as well (18). This study further confirmed these previous findings on the reverse signaling through membrane TNF-␣.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have already demonstrated that calcium mobilization and production of cytokines such as IFN-␥ and IL-2 was induced in HTLV-I-infected human T cells by the stimulation of membrane TNF-␣ (10,11). Moreover, ligation of soluble TNF receptor to membrane TNF-␣ has recently been shown to cause calcium mobilization in the mouse macrophage cell line, RAW267.4, as well (18). This study further confirmed these previous findings on the reverse signaling through membrane TNF-␣.…”
Section: Discussionsupporting
confidence: 89%
“…Upon activation of membrane TNF-␣ with anti-TNF-␣ Ab, IL-2 and IFN-␥ were induced with concurrent elevation of intracellular calcium concentration (10,11). This finding of calcium mobilization by membrane TNF-␣ was confirmed subsequently by others (18). Membrane TNF-␣ has also been shown to modulate anti-CD3-triggered T cell cytokine expression in mice (19).…”
supporting
confidence: 67%
“…This suggests that cross-linking of mTNF, in contrast to other TNF-like ligands, may not be mandatory for signal transduction. With regard to downstream signals, Watts et al provide evidence that casein kinase I phosphorylates the cytoplasmic domain of mTNF at a consensus sequence that is conserved among members of the TNF family (21). In addition, a phosphorylation site of mTNF at serine residues could be identified (22).…”
Section: Discussionmentioning
confidence: 99%
“…In T cells reverse signaling via FasL and TRAIL appears to enhance cellular activation, leading to better proliferation and cytokine production. Most interestingly, while many of these molecules and in particular FasL contain signaling or binding motifs in their cytoplasmic domains, for example, phosphorylation sites or SH3-binding domains, 36,37 TRAIL has only a very small cytoplasmic tail devoid of any recognizable signaling motifs. It is therefore currently completely unclear how the cytoplasmic tail of TRAIL can mediate this costimulatory effect.…”
Section: Trail: a Ligand Or A Receptor?mentioning
confidence: 99%